2017
DOI: 10.1088/1748-605x/aa6e27
|View full text |Cite
|
Sign up to set email alerts
|

Rhein and polydimethylsiloxane functionalized carbon/carbon composites as prosthetic implants for bone repair applications

Abstract: A major issue in bone tissue engineering is the selection of biocompatible materials for implants, to reduce unwanted inflammatory reactions and promote cell adhesion. Bone tissue growth on suitable biomedical implants can shorten recovery and hospitalization after surgery. Therefore, a method to improve tissue-implant integration and healing would be of scientific and clinical interest. In this work, we permeated polydimethylsiloxane (PDMS) into carbon/carbon (C/C) composites (PDMS-C/C) and then coated it wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…As a universal IEE platform, the AECD also has various other applications. For example, it could also potentially be used to treat urinary incontinence; if integrated with a strain sensor, the AECD could monitor the bladder function, and when pathological behavior occurs, it could electrically stimulate the bladder sensory afferents to normalize bladder function ( 71 ). After specific programming, the AECD can undertake any programmed action when facing various physiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a universal IEE platform, the AECD also has various other applications. For example, it could also potentially be used to treat urinary incontinence; if integrated with a strain sensor, the AECD could monitor the bladder function, and when pathological behavior occurs, it could electrically stimulate the bladder sensory afferents to normalize bladder function ( 71 ). After specific programming, the AECD can undertake any programmed action when facing various physiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…We used APT to implement wireless energy transfer and communication, taking into consideration the high biocompatibility of the AECD with the human body. The inner components are fully sealed by PDMS, which has high biocompatibility (71), and some scholars have demonstrated that these electronic devices encapsulated by PDMS have high hemocompatibility, low inflammation, and long-term usage potential (71)(72)(73). In addition, the PDMS materials also have strong biodurability, because scholars have tested that implants made of these materials would not fail within 32 years (74).…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric materials can generate electrical signals in response to mechanical stress , and can, therefore, stimulate the signaling pathways and promote tissue regeneration in the impaired sites, indicating that the application of piezoelectric materials in bone regeneration is feasible. , Piezoelectric materials can be classified into piezoelectric polymers and ceramics, such as poly­(vinylidene fluoride) (PVDF), poly­(vinylidene fluoridetrifluoroethylene) (PVDF-TrFE), polydimethylsiloxane (PDMS), and BaTiO 3 (barium titanate) . Piezoelectric polymers generally present superior biocompatibility, excellent cell adhesion, and growth facilitation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, surface modification of C/C composites has been extensively studied in the field of bone repair. 4,5 Many surface modification techniques have been used to prepare biomedical coatings and films of C/C composites, including plasma spraying, 6,7 electromagnetic deposition, 8 and magnetron sputtering. 9 Among them, polydopamine (PDA) coatings have attracted much interest due to the simple method of formation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, surface modification of C/C composites has been extensively studied in the field of bone repair. 4,5…”
Section: Introductionmentioning
confidence: 99%